Prototype Topology SDN for Simple Network Campus - Arnes Yuli Vandika (International Conference on Engineering and Technology Development (ICETD), 2014)
The use of communication networks is increasingly felt increasingly sophisticated. This can be seen with the use of innovative network infrastructure that provides connection services to users. Virtual service network can be a prototype of a software-based network logic in this case is a software-defined network. This software is open source-based or a lot of the paid version. Where this software serves as a bridge between networks that use routers or router software logic. Using a software-defined network on the router logic can be made very flexible and easy to integrate with a stable condition.